Чернігівський Спасо-Преображенський собор у реаліях міського соціуму (1943–1960 рр.) - Ванжула, О.М. (Сіверщина в історії України, 2020)
Стаття присвячена маловідомому періоду (1943–1960 рр.) з історії чернігівського Спасо-Преображенського собору, коли пам’ятка перебувала в користуванні православної релігійного громади.
Проаналізовано стан соборної громади у післявоєнний час та місце давньоруського храму в забудові історичної частини Чернігова.
Залучені архівні джерела надають можливість розкрити питання кількісного, особового складу православної громади та соборної
ради. Уперше оприлюднені дані про прибутки та витрати громади
на проведення ремонтних робіт, утримання церковного хору кафедрального собору тощо. Розкрито бюрократичний процес вилучення собору з користування православної соборної громади в контексті загальнодержавної антирелігійної кампанії 1958–1960 рр.
Окреслено формальні та реальні причини вилучення Спасо-Преображенського собору з користування релігійної громади. The article is devoted to insufficient explored period (1943-1960) in
the history of the the Cathedral of the Transfiguration of Our Saviour in
Chernihiv. The status of the Cathedral in the first half of the 20th century
was changing according to the global socio-political transformations: the
functional Cathedral in Chernihiv during 1919–1926; since 1929 – the
Museum of Chernihiv State Reserve; during 1936-1940 – warehouse. From
the beginning of the Nazi occupation in Chernihiv (1941) the churches and
monasteries, that were closed by bolshevists, were opened. The Cathedral
of the Transfiguration of Our Saviour which was the sacral sacred place
of Ukraine had a special value among the other 6 churches that were open
in the city. After liberation of Chernihiv (1943) the Cathedral was in the
enjoyment of Orthodox community. During a short-term period of «de-
Stalinization» the regime behaved liberally toward the church. In 1949 the
Cathedral was repaired at the cost of eparchy. The staff of the Cathedral
consisted of 3 or 4 priests, 2 diakons and 2 protodeacons. The change of party
management of the country marked the next stage of atheistic campaign
against the Church which was resulted in new period of widespread closing
of the monasteries and churches. The location of the Cathedral of the
Transfiguration of Our Saviour in the center of municipal park of culture
and rest didn’t fit in the ideological stereotypes of Soviet society. On the
back of the All-Soviet Union atheistic campaign (1958-1964) municipal
and regional government bodies came forward with initiative on closing
of the Cathedral. Formally the ostensible purpose of the withdrawal of
the Cathedral of the Transfiguration of Our Saviour in Chernihiv from the
use of Orthodox community was the necessity of comprehensive scientific
research of the unique Old Rus monument. The practical reason of closing
the Cathedral was the strengthening of political and ideological voluntarism
in the country that resulted in liquidation of religious organizations. In
the totalitarian state, where the policy towards building communism was
declared, there was no place for religion as public ideology.